Opioid sparing anaesthesia using dexmedetomidine in a morbidly obese patient with mandibular tumor requiring free fibular graft reconstruction surgery - Singla, Karan; Sen, Indu; Gaba, Sunil (International Journal of Research in Medical Sciences, 2020)
A 45 year old male diagnosed as a case of Ameloblastoma mandible, requiring mandibular reconstruction with a Free Fibular Flap graft was planned under general anaesthesia (GA).